New Glances on the Murals of the Augustinian Convent of Malinalco, New Spain, 16th Century - von Wobeser, Gisela (2018)
The present article proposes to revise the interpretations that to date exist about the murals of the under cloister of the Augustinian convent of Malinalco (Mexico), made by indigenous people in the 16th century, by means of the grisaille technique. In it, the idea of representing the heavenly paradise or the earthly paradise is refuted, and it is suggested that the iconographic program focuses on the 12 monumental shields, alluding to the names of Jesus, Mary and the emblem of the Augustinian order. Likewise, the ornamental importance of the phytomorphic and zoomorphic motifs that accompany the shields and that dominate visually within the group is highlighted. It is noted that the sources for the realization of the different motifs that make up the murals are very diverse and come from Europe, American codices and the natural environment of Malinalco. Finally, the epigraphic frieze is analyzed, and it is suggested that the main purpose of the murals was to praise God, with the hope of eternal salvation.